A practical asymptotic variance estimator for two-step semiparametric estimators - Daniel Ackerberg; Xiaohong Chen; Jinyong Hahn (Centre for Microdata Methods and Practice (cemmap), 2010)
The goal of this paper is to develop techniques to simplify semiparametric inference. We do this by deriving a number of numerical equivalence results. These illustrate that in many cases, one can obtain estimates of semiparametric variances using standard formulas derived in the already-well-known parametric literature. This means that for computational purposes, an empirical researcher can ignore the semiparametric nature of the problem and do all calculations as if it were a parametric situation. We hope that this simplicity will promote the use of semiparametric procedures.
Keywords: C14; 330; Nichtparametrisches Verfahren